Oil plant genomes : current state of the science - Song, Jia-Ming (2021)
Vegetable oils are indispensable nutritional components of human diet as well as important raw materials for a variety of industrial applications such as pharmaceuticals, cosmetics, oleochemicals and biofuels. The oil plant genomes are highly diverse, and the genetic variation leads to the diversity in oil biosynthesis and accumulation along with agronomic traits. This review discusses the plant oil biosynthetic pathways, the current state of genome assembly, the polyploidy and asymmetric evolution genomes of oil plants and their wild relatives, and the research progress of pan-genomics in oil plants. The availability of complete high-resolution genomes and pangenomes has enabled the identification of structural variations in the genomes that are associated with the diversity of agronomic and environment fitness traits. These and more future genomes also provide powerful tools to understand crop evolution and to harvest the rich natural variations to improve oil crops for enhanced productivity, oil quality, and adaptability to changing environments.